Patience and Adjustment for New Students In Darussa'adah Teupin Raya Islamic Boarding School Aceh - Safrilsyah Safrilsyah; Nazila Ulfa; Karjuniwati Karjuniwati; Barmawi Barmawi (Psychosophia: Journal of Psychology, Religion, and Humanity, 2022)
The concept of patience can be categorized as one of the topics of study in positive psychology, such as gratitude and forgiveness. Self-adjustment is one of the abilities that must be possessed by every individual. In everyday life, individuals usually use certain ways that are acceptable to their environment to adjust to the goal of being able to meet and satisfy their needs. This study aims to determine the relationship between patience and adjustment to new students at the Darussa'adah Islamic Boarding School Teupin Raya. This study uses a quantitative-correlation method. The sample amounted to 300 new students with a sampling technique based on the proportionate stratified random sampling technique. This study uses two scales, namely: the patience scale (32 items) which refers to the patience aspect of Subandi (2011) with a reliability coefficient value of r = 0.860, and the self-adjustment scale (40 items) which refers to the self-adjustment aspect of (Desmita, 2009) with a reliability coefficient value of r = 0.918. The results of this study indicate that the value of the correlation coefficient between patience and adjustment to new students at the Darussa'adah Islamic boarding school Teupin Raya is r = 0.970 with p = 0.000. This means that there is a very significant relationship between patience and adjustment to new students at the Darussa'adah Islamic Boarding School Teupin Raya.